Viral vectored hepatitis C virus vaccines generate pan-genotypic T cell responses to conserved subdominant epitopes - Donnison, T; von Delft, A; Brown, A; Swadling, L; Hutchings, C; Hanke, T; Chinnakannan, S; Barnes, E (Elsevier, 2020)
Background: Viral genetic variability presents a major challenge to the development of a prophylactic hepatitis C virus (HCV) vaccine. A promising HCV vaccine using chimpanzee adenoviral vectors (ChAd) encoding a genotype (gt) 1b non-structural protein (ChAd-Gt1b-NS) generated high magnitude T cell responses. However, these T cells showed reduced cross-recognition of dominant epitope variants and the vaccine has recently been shown to be ineffective at preventing chronic HCV. To address the challenge of viral diversity, we developed ChAd vaccines encoding HCV genomic sequences that are conserved between all major HCV genotypes and adjuvanted by truncated shark invariant chain (sIitr).